Socializing from a Distance in a Community Music Ensemble During the COVID-19 Pandemic - Rowan, Brent (Critical Studies in Improvisation / Études critiques en improvisation, 2021)
Music Director Brent Rowan describes the impact of the COVID-19 pandemic on the New Horizons Band Guelph program for older adults.